Mitochondrial stress induced by continuous stimulation under hypoxia rapidly drives T cell exhaustion - Scharping, Nicole E.; Rivadeneira, Dayana B.; Menk, Ashley V.; Vignali, Paolo D. A.; Ford, B. Rhodes; Rittenhouse, Natalie L.; Peralta, Ronal; Wang, Yiyang; Wang, Yupeng; DePeaux, Kristin; Poholek, Amanda C.; Delgoffe, Greg M. (Nature immunology, 2021)
Cancer and chronic infections induce T cell exhaustion, a hypofunctional fate carrying distinct epigenetic, transcriptomic and metabolic characteristics. However, drivers of exhaustion remain poorly understood. As intratumoral exhausted T cells experience severe hypoxia, we hypothesized that metabolic stress alters their responses to other signals, specifically, persistent antigenic stimulation. In vitro, although CD8 + T cells experiencing continuous stimulation or hypoxia alone differentiated into functional effectors, the combination rapidly drove T cell dysfunction consistent with exhaustion. Continuous stimulation promoted Blimp-1-mediated repression of PGC-1α-dependent mitochondrial reprogramming, rendering cells poorly responsive to hypoxia. Loss of mitochondrial function generated intolerable levels of reactive oxygen species (ROS), sufficient to promote exhausted-like states, in part through phosphatase inhibition and the consequent activity of nuclear factor of activated T cells. Reducing T cell–intrinsic ROS and lowering tumor hypoxia limited T cell exhaustion, synergizing with immunotherapy. Thus, immunologic and metabolic signaling are intrinsically linked: through mitigation of metabolic stress, T cell differentiation can be altered to promote more functional cellular fates. Delgoffe and colleagues show that continuous TCR signaling and hypoxia increase Blimp-1, which suppresses PGC-1α-dependent mitochondrial reprogramming and increases reactive oxygen species generation. Such conditions promote T cell exhaustion.